1985
DOI: 10.1038/icb.1985.13
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection With Murray Valley Encephalitis Virus. Pigs, Cattle, Sheep, Dogs, Rabbits, Macropods and Chickens

Abstract: Summary A tool of 142 young animals including 10 domestic and 14 feral pigs, 12 Hereford calves, 12 crossbred and 24 Merino lambs, 11 dogs, 8 domestic and 16 feral rabbits, 14 Grey kangaroos, 9 Agile wallabies and 12 chickens was exposed to infection with 4 strains of Murray Valley encephalitis virus (MVE), mainly using orally infected Culex annulirostris mosquitoes. In terms of their viraemic response, the animals were grouped into high (Grey kangaroos, rabbits), moderate (pigs, dogs, chickens) and low (calve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
2

Year Published

1985
1985
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 5 publications
(5 reference statements)
4
20
2
Order By: Relevance
“…Rabbits may be a promising alternative model for studying the pathogenesis and immune response to WNV challenge, since previous experimental studies using cottontail rabbits have found a moderate acute viraemia, but with no morbidity or mortality [211]. Similar findings were observed when New Zealand White rabbits (NZWRs) were infected with a closely related flavivirus, MVEV [212]. Other possible alternatives for investigation include guinea pigs and ferrets, which have been used as small animal models for immunologic investigation with JEV [213] and other infectious agents such as influenza [214].…”
Section: Animal Models For Wnv Pathogenesis and Immune Control Investsupporting
confidence: 67%
See 2 more Smart Citations
“…Rabbits may be a promising alternative model for studying the pathogenesis and immune response to WNV challenge, since previous experimental studies using cottontail rabbits have found a moderate acute viraemia, but with no morbidity or mortality [211]. Similar findings were observed when New Zealand White rabbits (NZWRs) were infected with a closely related flavivirus, MVEV [212]. Other possible alternatives for investigation include guinea pigs and ferrets, which have been used as small animal models for immunologic investigation with JEV [213] and other infectious agents such as influenza [214].…”
Section: Animal Models For Wnv Pathogenesis and Immune Control Investsupporting
confidence: 67%
“…Interestingly, the viraemia peaks observed in our study were lower than those reported in previous flavivirus infection studies in rabbits (peak ~10 1−3 TCID 50 equivalent or PFU/mL, as compared to ~10 4−5 CID 50 /mL or SMIC LD 50 /mL) [211,212]. This may be explained by the different experimental conditions involved, such as the use of different WNV strains [211], route of inoculation [212], trapping region for CTRs (e.g., Iowa…”
Section: Wnv Kineticscontrasting
confidence: 53%
See 1 more Smart Citation
“…No agent was isolated from organs of these mice when inoculated into litters of suckling mice. In order to get enough blood for testing, the mice were sacrificed at 7 d. DISCUSSION This paper on the response of animals to MVE infection complements that of Kay et al (1985). The animal species were selected on the basis of their abundance, distribution, habits and attractiveness to the major vector Cx annulirostris.…”
Section: Wild Micementioning
confidence: 99%
“…Our data on the persistence of HI antibodies in the 3 psittaciforms and the anseriform species tested are comparable with that of Rufous night herons. Little egrets and with most other animal species tested (Kay et al, 1985). However, it now seems apparent that within any species poor immunological responders do occur.…”
Section: Wild Micementioning
confidence: 99%